ANALISIS POTENSI DAERAH BERDASARKAN PRODUK DOMESTIK REGIONAL BRUTO MENGGUNAKAN METODE LOCATION QUETIENT ( LQ ) DAN TIPOLOGI KLASSEN DI KOTA SUNGAI PENUH: Adek Irma Rosi, Zesmi Kusmila - IrmaRosi, Adek; Kusmila, Zesmi (JURNAL ADMINISTRASI NUSANTARA, 2023)
This research aims to find out what economic sectors are the base and non-base sectors of Sungai Full City, and which sectors have the potential to be developed in Sungai Full City. The analytical methods used in this research are the Location Quotient (LQ) analysis method and the Klassen typology analysis method. The results of the research concluded that thirteen sectors included basic sectors with an LQ value > 1, while there were four non-basic sectors. Furthermore, of the seventeen sectors in the city of Sungai Banyak, there are seven sectors that are developed and growing fast and six sectors that are developed but depressed, two sectors that are developing quickly or have potential and finally two sectors are relatively underdeveloped.